D-serine released by astrocytes in brainstem regulates breathing response to CO2 levels - S. Beltrán-Castillo (Nature Portfolio, 2017)
Astrocytes are involved in chemoreception in brainstem areas that regulate breathing rhythm, and astrocytes are known to release d-serine. Here the authors show that astrocyte release of d-serine contributes to CO2 sensing and breathing in brainstem slices, and in vivo in awake unrestrained mice.